Patients' and healthcare providers' perceptions of a mobile portal application for hospitalized patients. Issue 1 (December 2016) - O'Leary, Kevin; Sharma, Rashmi; Killarney, Audrey; O'Hara, Lyndsey; Lohman, Mary; Culver, Eckford; Liebovitz, David; Cameron, Kenzie
Abstract Background Hospital-based patient portals have the potential to better inform and engage patients in their care. We sought to assess patients' and healthcare providers' perceptions of a hospital-based portal and identify opportunities for design enhancements. Methods We developed a mobile patient portal application including information about the care team, scheduled tests and procedures, and a list of active medications. Patients were offered use of tablet computers, with the portal application, during their hospitalization. We conducted semi-structured interviews of patients and provider focus groups. Text from transcribed interviews and focus groups was independently coded by two investigators using a constant comparative approach. Codes were reviewed by a third investigator and discrepancies resolved via consensus. Results Overall, 18 patients completed semi-structured interviews and 21 providers participated in three focus groups. Patients found information provided by the portal to be useful, especially regarding team members and medications. Many patients described frequent use of games and non-clinical applications and felt the tablet helped them cope with their acute illness. Patients expressed a desire for additional detail about medications, test results, and the ability to record questions. Providers felt the portal improved patient engagement, but worried that additional features might result in a volume and complexity of information that could be overwhelming for patients. Providers also expressed concern over an enhanced portal's impact on patient-provider communication and workflow. Conclusions Optimizing a hospital-based patient portal will require attention to type, timing and format of information provided, as well as the impact on patient-provider communication and workflow.